Understanding what wellbeing means to medical and nursing staff working in paediatric intensive care: an exploratory qualitative study using appreciative inquiry. Issue 4 (1st April 2022) - Butcher, Isabelle; Morrison, Rachael; Webb, Sarah; Duncan, Heather; Balogun, Omobolanle; Shaw, Rachel
Abstract : Aims and objectives: To explore what wellbeing means to medical and nursing staff working in a large paediatric intensive care (PIC). Design: Exploratory qualitative design using an appreciative inquiry framework. Setting: PIC unit; primary, secondary and tertiary. Participants: 46 nurses and doctors working on PIC. Interventions: A set of images were used together with open-ended questions to prompt staff to discuss what wellbeing means to them. Interviews were audiorecorded and transcribed. Data were analysed thematically. Results: Images depicting nature, children and groups of adults were selected most. Meanings of wellbeing for PIC staff can be understood through three themes: (1) Being nurtured and supported at work, (2) Importance of nature and (3) Social support independent of work. The first theme considered the importance of being listened to at work as well as staff highlighting the value of being in control at work. Within the second theme, being active in nature and outdoors as well as the importance of being in the present moment was illustrated. Within the final theme, staff expressed the value of having support independent of work and highlighted the importance of spending time with family. Conclusions: This study provides a unique insight into how individuals working in PIC experience wellbeing and what wellbeing means to them. Understanding how healthcare professionals in PIC settings experience wellbeing and what wellbeing means to them will enable researchers to develop interventions designed to enhance staff wellbeing based on lived experience.